Correlations between Serum P2X7, Vitamin A, 25‐hydroxy Vitamin D, and Mycoplasma Pneumoniae Pneumonia. Issue 5 (16th March 2021) - Meng, Fanjun; Chen, Ping; Guo, Xiaolong; Li, Xiaoru; Wu, Yuexuan; Liu, Wenen; Jiang, Feng; Liu, Huan; Wang, Lixin
Abstract: Background: Identifying new molecular diagnostic markers for Mycoplasma Pneumoniae Pneumonia (MPP) has always been an essential topic since MPP cases have increased every year, especially among children. Here, we examined the correlation between serum level of Purinergic receptor P2X7, vitamin A, and 25‐hydroxy vitamin D (25(OH)D) and the severity of MPP, aiming to identify molecules that have the potential to become diagnostic markers. Methods: This study was conducted on 186 cases aged 1–14 (136 MPP and 50 non‐MPP patients). Serum levels of Purinergic receptor P2X7, vitamin A, 25(OH)D, and multiple inflammatory and immune factors were measured, compared, and tested for statistical significance. Results: Serum P2X7, tumor necrosis factor‐α (TNF‐α), and interleukin‐1β (IL‐1β) levels were significantly increased in severe MPP patients, while serum vitamin A, 25(OH)D, IgA, and IgG levels were significantly decreased. Conclusion: Our results demonstrated a positive correlation between serum P2X7 level and the severity of MPP, and negative correlations between serum levels of vitamin A and 25(OH)D and the severity of MPP, suggesting that high serum levels of P2X7 and low serum levels of vitamin A and 25(OH)D may indicate relatively severer MPP.